2021
DOI: 10.3390/ijerph18020415
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimisation in Early Childhood; Observations of Participant Roles and Sex Differences

Abstract: During middle childhood and adolescence, victimisation appears to be a group process involving different participant roles. However, peer reports with younger children (four to six years old) have failed to identify the participant roles of assistant (to the bully) reinforcers or defenders with much reliability. This may be because peer victimisation is a more dyadic process among younger children (behavioural reality), or because of limitations in young children’s cognitive capacity to identify these behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Bullying behaviors are characterized by a developmental trajectory (Cook et al, 2010) and increase over the years from childhood, with a peak during early adolescence (Hymel & Swearer, 2015;Menesini & Salmivali, 2017). In addition, research has shown that, starting from middle childhood, bullying and victimization start to be group processes (Monks et al, 2021) and are driven by status goals (Salmivalli, 2010). Older students might turn to bullying more than younger students because this could lead to an improvement in their social status.…”
Section: Peer Status Bullying and Agementioning
confidence: 99%
“…Bullying behaviors are characterized by a developmental trajectory (Cook et al, 2010) and increase over the years from childhood, with a peak during early adolescence (Hymel & Swearer, 2015;Menesini & Salmivali, 2017). In addition, research has shown that, starting from middle childhood, bullying and victimization start to be group processes (Monks et al, 2021) and are driven by status goals (Salmivalli, 2010). Older students might turn to bullying more than younger students because this could lead to an improvement in their social status.…”
Section: Peer Status Bullying and Agementioning
confidence: 99%
“…Similarly, Monks et al (2021), in an observational study of 56 children aged four to five years old, have also documented that sex differences were observed in types of aggression displayed by children, with boys more likely to than girls to be physically aggressive. Likewise, children were less likely to be aggressive with other-sex peers and were most likely to be victimised by children of the same sex as them.…”
Section: Introductionmentioning
confidence: 80%
“…. This cognitive ability is a key skill needed to deeply understand bullying, which is an attempt to gain social status within the peer group (Monks et al 2021), as it allows bullies to understand the impact on the bystanders feelings and thoughts about the victims' feelings and thoughts while being bullied. When a bully is victimizing a classmate, he or she is sending a subtle message to the other classmates, letting them know who is in charge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations